PROBLEMATIKA PEMBELAJARAN BERBASIS DARING IMPLIKASINYA TERHADAP KEMURNIAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM - Arifin, Nur Alam; Saputra, Eddy; Wulan, Rayung (Pascasarjana Universitas Islam Jakarta, 2022)
Online based learning is a learning process that must be carried out amid social distancing. In Indonesia, this method is known as PJJ (distance learning). Online-based learning is a must for students and teachers to keep the learning process going. While on the other hand, there are still many students and parents who are not fully able to use smartphones and laptops to the fullest. In order for online learning to be carried out, smartphones and laptops must be supported by an internet network, while in areas students still complain that signals are difficult to obtain, this is due to the uneven distribution of infrastructure for Internet Network. With the long distance between students and teachers, online-based learning methods have implications in producing purity in the assessment of learning outcomes. This study uses qualitative methods, the data sources will be generated through observation, interviews and information from print and electronic media. The purpose of this study is to provide input on the problems of online-based learning. If in the future the online-based learning method becomes an option, careful planning and preparation are needed so that its implementation can run as it should. Online based learning is a learning process that must be carried out amid social distancing. In Indonesia, this method is known as PJJ (distance learning). Online-based learning is a must for students and teachers to keep the learning process going. While on the other hand, there are still many students and parents who are not fully able to use smartphones and laptops to the fullest. In order for online learning to be carried out, smartphones and laptops must be supported by an internet network, while in areas students still complain that signals are difficult to obtain, this is due to the uneven distribution of infrastructure for Internet Network. With the long distance between students and teachers, online-based learning methods have implications in producing purity in the assessment of learning outcomes. This study uses qualitative methods, the data sources will be generated through observation, interviews and information from print and electronic media. The purpose of this study is to provide input on the problems of online-based learning. If in the future the online-based learning method becomes an option, careful planning and preparation are needed so that its implementation can run as it should.